The symbols of heraldry in today's political theatrics. The Russian case of the letter ‘Z’ and the St. George ribbon: El caso ruso de la letra “Z” y la cinta de San Jorge - Gelpí Rodríguez, Maria (Eikón / Imago, 2025)
This article analyzes the role of legitimizing symbols of war in contemporary political theatricality. It focuses on the case of Russia and the Latin letter "Z", initially painted on the tanks of Russian troops at the beginning of the invasion of Ukraine in 2022, with the same function as the old coats of arms, namely the recognition of the contender. Later, this letter has been used in the media to symbolize support for Russia in the war in Ukraine, in the urban context of civil society, especially configured with the colors of the St. George ribbon, of heraldic origin. This study examines Vladimir Putin's most relevant speeches, his public appearances, as well as support through social networks and merchandising products. The social impact of the use of symbols is evaluated, in the political and urban sphere, along with other strategies.